Variation in Lipid Content and Glyceride Compositions of Four Different Varieties of Corn (Zea mays L.) Oil (Bangladesh Journal of Scientific and Industrial Research, 2007)
Oil extracted from four different varieties of corn (Zea mays) were evaluated in terms of lipid, glyceride and fatty acid compositions. The total lipid extracts were fractionated into lipid classes by silicic acid chromatography. The neutral lipids were found to be 96.80 - 97.50 %; glycolipid 1.50-1.66 %; phospholipid 0.80-0.95 % respectively. The fatty acid composition of triglyceride (TG) fraction was analysed by gas liquid chromatography (GLC). The percentage composition of fatty acid were found to be linoleic acid 35.62 to 49.5 %, palmitic acid 8.7 to 9.9 %, stearic acid 1.9 to 2.3 %, myristic acid 0.9 to 1.6 % and linolenic acid 0 to 2.2 %. Bangladesh J. Sci. Ind. Res. 42(2), 223-228, 2007